O uso do Geogebra 3D e a aprendizagem significativa da geometria espacial no ensino médio - Silva, Quezia de Oliveira Vargas da (2017)
The present work presents a research carried out with third grade students of the regular high school of the state network of Rio de Janeiro. The study admits, by base, the insertion of the GeoGebra 3D software as a technological resource to be used by the students, where it is investigated its contribution to Significant Learning regarding the concepts of Space Geometry. The main objective is to search strategies that enhance the teaching of Space Geometry involving the concepts of prisms, pyramids, cones, cylinders and sphere. we present as a specific objective the construction of the educational product with the intention of contributing to the teaching of mathematics in basic education. The methodology is classified as qualitative of exploratory character. We observed through the procedures that it is essential to search for activities that arouse in the student the desire to acquire geometric knowledge, to understand these concepts significantly and to use them correctly, which required active participation of the students, where they carry out the pedagogical action.